Development and Feasibility of a Regulated, Supramaximal High-Intensity Training Program Adapted for Older Individuals - Hedlund, Mattias; Lindelöf, Nina; Johansson, Bengt; Boraxbekk, Carl-Johan; Rosendahl, Erik (Frontiers in Physiology, 2019)
Background: High-intensity training (HIT) with extremely short intervals (designated here as supramaximal HIT) is a time-efficient training method for health and performance. However, a protocol for regulation and control of intensity is missing, impeding implementation in various groups, such as older individuals. Method: This study presents the development and characteristics of a novel training protocol with regulated and controlled supramaximal intervals adapted for older people. Using both quantitative and qualitative analyses, we explored the feasibility of the program, performed as group training, with physically active older individuals (aged 65–75, n=7; 5 women). The developed supramaximal HIT program consisted of 10 × 6 second cycle sprint intervals with 1 minute of active recovery with the following key characteristics: (1) an individual target power output was reached and maintained during all intervals and regulated and expressed as the percentage of the estimated maximum mean power output for the duration of the interval (i.e., 6 seconds); (2) pedaling cadence was standardized for all participants, while resistance was individualized; and (3) the protocol enabled controlled and systematic adjustments of training intensity following standardized escalation criteria. Aim: Our aim was to test the feasibility of a novel training regimen with regulated and controlled supramaximal HIT, adapted for older people. The feasibility criteria for the program were to support participants in reaching a supramaximal intensity (i.e., >100% of estimated VO2 max), avoid inducing a negative affective response, and have participants perceive it as feasible and acceptable. Results: All feasibility criteria were met. The standardized escalation procedure provided safe escalation of training load up to high, supramaximal intensity (around three times the power output at estimated VO2 max). The participants never reported negative affective responses, and they perceived the program as fun and feasible. Conclusion: This novel program offers a usable methodology for further studies on supramaximal HIT among older individuals with different levels of physical capacity. Future research should explore the effects of the program in various populations of older people and their experiences and long-term adherence compared with other forms of training.